INCREASE OF STRESS RESISTANCE OF TEACHERS OF HIGHER MEDICAL EDUCATIONAL ESTABLISHMENTS - Самойленко, Олена; Дубина, Сергій (SWorldJournal, 2023)
High level of modern stressogenesis in socio-cultural conditions of a person's life affects all areas of our existence. Stress factors encourage the development and formation of stress resistance of the personality. The fast-flowing rhythm of the informat